Writing as a way towards a possible handcraft of the subject: an approach from the feminine jouissance - González Fernández, Cristina (Escritura e Imagen, 2024)
This essay pretends to be a reflection on the subjective implications of writing. To this purpose, it will start from some of the concepts that constitute the last part of Jacques Lacan’s psychoanalytic theory, such as "letter" and "feminine jouissance". Once these concepts are deployed, it will be possible to approach the question of writing as a form of organization of the void inscribed in the mode of jouissance non-all, which will open the possibility of thinking of it as a process with repercussions on the subject through the erosion caused by the unveiling of semblants. The reflection will be reinforced by philosophical and literary works that also address this question of writing.